2001
DOI: 10.1002/ana.1119
|View full text |Cite
|
Sign up to set email alerts
|

Nigrostriatal collaterals to thalamus degenerate in parkinsonian animal models

Abstract: Movement, cognition, emotion, and positive reinforcement are influenced by mesostriatal, mesocortical, and mesolimbic dopamine systems. We describe a fourth major pathway originating from mesencephalic dopamine neurons: a mesothalamic system. The dopamine transporter, specific to dopamine containing axons, was histochemically visualized in thalamic motor and limbic-related nuclei and regions that modulate behavioral state as opposed to sensory nuclei in rats, nonhuman primates, and humans. Anatomical tracing e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
68
0
4

Year Published

2003
2003
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 53 publications
2
68
0
4
Order By: Relevance
“…The vPAG dopaminergic projections to the prefrontal cortex Yoshida et al, 1989) and the midline and intralaminar thalamus (Takada et al, 1990;Freeman et al, 2001) have been identified previously. The dopamine transporter (Freeman et al, 2001) and D 1 and D 2 dopamine receptors (Huang et al, 1992;Lewis and O'Donnell, 2000) are present in both the thalamus and the cerebral cortex, suggesting that dopamine can directly influence thalamocortical activity.…”
Section: Technical Considerationmentioning
confidence: 80%
See 1 more Smart Citation
“…The vPAG dopaminergic projections to the prefrontal cortex Yoshida et al, 1989) and the midline and intralaminar thalamus (Takada et al, 1990;Freeman et al, 2001) have been identified previously. The dopamine transporter (Freeman et al, 2001) and D 1 and D 2 dopamine receptors (Huang et al, 1992;Lewis and O'Donnell, 2000) are present in both the thalamus and the cerebral cortex, suggesting that dopamine can directly influence thalamocortical activity.…”
Section: Technical Considerationmentioning
confidence: 80%
“…Despite this evidence, the specific population of dopaminergic neurons responsible for arousal is not known. VTA neurons that project to the prefrontal cortex and striatum (Steinfels et al, 1983;Freeman et al, 2001) are often assumed to play this role; however, the firing of VTA neurons or SN neurons that project to the striatum does not correlate with overall levels of behavioral wakefulness in rats (Miller et al, 1983). Furthermore, neurotoxic lesions of the VTA do not decrease behavioral wakefulness (Lai et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Como a dopamina nigral possui efeito inibitório no NRT 6,7 , o seu aumento gera uma diminuição na ativação dos neurônios desta região. No contexto do modelo, isso faz com que a área talâmica T y sofra menos inibição oriunda do NRT.…”
Section: Métodounclassified
“…A formação do foco atencional passa pelo controle do circuito tála-mo-cortical, uma vez que o tálamo seleciona os estí-mulos externos a serem processados pelo córtex 4,5 . Experimentos histoquímicos realizados por Freeman et al 6 , tanto em humanos como em macacos, mostraram que a SN projeta, através da via mesotalâmica, neurô-nios dopaminérgicos em direção a núcleos talâmicos -em particular o núcleo reticular talâmico (NRT). Com isso, a SN possivelmente afeta diretamente a atividade do circuito tálamo-cortical e, portanto, modula a maneira pela qual o foco de atenção é consolidado.…”
unclassified
See 1 more Smart Citation